Miljökonsekvensbeskrivning för en utökning av befintlig djurhållning - Cedergren, Aron (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
In the last few years the environment becomes more watchful, even for us farmers. All agricultural enterprises that exceed 200 animal units must be tested according to regulation of environment. A farm business with 200 animal units and more is classed "environmentally hazardous activities" and has to make an environmental impact assessment for the business you have today, and the activity after expansion. Before you can construct a building and expand the numbers of animals is a lot of applications to make. I have in this project restricted me to establish a environmental impact assessment and a consultation foundation. To make a environmental impact assessment is the big part of the application. The environmental impact assessment take a lot of time and you need skills for all the rules in the environmental code to be abele to make an environmental impact assessment approved. The environment codes purposes (1 kap 1 § Miljöbalken) is to rule the laws. The purpose of the environment code is to promote sustainable development which will assure a healthy and sound environment for present and future generations. Definitions of a "environmentally hazardous activities" 9 kap 1§ Miljöbalken) shall mean the discharges of wastewater, solid matter or gas from land, buildings or structures onto land or into water areas or ground water. Or any entails a risk of detriment to human health or the environment due to discharges or emissions to pollution of land, air, water areas.